2017
DOI: 10.1080/09571736.2016.1258721
|View full text |Cite
|
Sign up to set email alerts
|

Emergent multilinguals learning languages with the iPad app iTEO: a study in primary schools in Luxembourg

Abstract: The present small-scale study investigates language learning in primary schools in Luxembourg and the ways in which this process is mediated by peers and the iPad app iTEO. This study draws its data from the larger longitudinal qualitative research project iTEO (2013)(2014)(2015)(2016)(2017) and is based on 13 hours of audio and video-recordings. The participants are 6-7-year-olds learning German and French. Grounded in sociocultural theory, this paper examines, first, the ways in which the emergent multilingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The primary teacher valued the development of language awareness and conscious reflection on language that came from the children giving each other feedback on their oral productions. He viewed iTEO as a flexible 'language learning tool' (Kirsch & Bes, 2017;Kirsch & Gretsch, 2015, p. 45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary teacher valued the development of language awareness and conscious reflection on language that came from the children giving each other feedback on their oral productions. He viewed iTEO as a flexible 'language learning tool' (Kirsch & Bes, 2017;Kirsch & Gretsch, 2015, p. 45).…”
Section: Discussionmentioning
confidence: 99%
“…In Luxembourg, Gretsch and Kirsch researched the use of iTEO after the completion of the piloting phase of the app in 2012. Kirsch and Bes (2017) found that the 6-7-year-olds collaboratively constructed oral texts on iTEO and provided each other with feedback that led to the learning of new words and sentence structures. While the above-mentioned studies on storytelling apps indicate that children collaborated, they did not shed light on the learners' use of language(s) while producing stories.…”
Section: Fostering Collaboration and Developing Speaking Skills Throumentioning
confidence: 99%
“…Mobile technologies have the potential to motivate learners, increase their engagement, widen opportunities for meaningful interactions, and connect formal and informal learning environments ( Karsenti & Fievez, 2013 ; Kukulska-Hulme, 2013 ; Martin-Beltrán et al., 2017 ). However, studies have also indicated that teachers are unsure of how to use these tools effectively to promote dialogue ( Mercer et al., 2019 ) and support learning ( Karsenti & Fievez, 2013 ; Kirsch & Bes, 2017 ). Teachers appear to use new technologies based on teacher-led pedagogies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Schreiber, 2015: 83 f.), the amount of multilingual CALL studies with a school focus published in these four journals is very limited. This is not to say, of course, that such studies do not exist, just that they are not published in these four journals (cf., e.g., Alvarez, 2018;Brunsmeier & Kolb, 2018;Cutrim Schmid, 2018;Dausend, 2018;Elsner & Buendgens-Kosten, 2018;Kirsch & Bes Izuel, 2019;Lohe, 2018).…”
Section: Resultsmentioning
confidence: 99%